Environmental perspectives of fine grounded concrete powder: LCA case study of light-weight concrete block - Jan Pešta (Acta Polytechnica CTU Proceedings, 2022)
The construction elements produced with low demand for primary resources are being developed in the building industry. However, not only consumption of primary resources but also environmental impacts of such products should be considered to increase the sustainability of the construction industry. To investigate the environmental impacts of lightweight concrete blocks, life cycle assessment (LCA) was used as an analytical tool according to the EN 15 804 + A2. Firstly, the properties of fine grounded concrete powder (FRWC) were measured to declare functionality and potential to use of the considered product. Then, the lightweight concrete block containing FRWC was designed. The potential environmental impacts of the lightweight concrete block were assessed for the following phases: raw material production, transport of materials, production of concrete block, and end of life of the block. The considered system boundaries includes the production of fine grounded concrete powder, which was produced by recycling demolished concrete structures. The results were related to 1 tun of lightweight concrete block. Unsurprisingly, the calculated impact is mainly influenced by cement production. The total impact of the life cycle of 1 t of the lightweight block is 336 kg CO2 eq. On the other hand, the lightweight block reached better results in the comparison with the Aerated Autoclaved Concrete block in most of the categories.